Study on the Tissue Heterogeneity and Micromechanical Properties of Maize Kernel - Zhou Shi; Jingcun Bi; Peng Xu; Rui Li; Guohai Zhang; Duanyang Geng; Yubin Lan; Bolong Wang (Agriculture)
This study measures and analyzes the heterogeneity and mechanical properties of maize kernels at the microscopic scale. Through microscopic tissue analysis and mechanical property tests, it was found that there are significant differences in the mechanical properties of different tissues in maize kernels. The starch granules in the horny endosperm are regular polyhedra, closely arranged, with a high number of proteins tightly filling the gaps between starch granules. The structural characteristics of the horny endosperm give it a high maximum rupture force and elastic modulus, with a maximum rupture force of 128 N and an elastic modulus of 353 MPa. The starch granules in the farinaceous endosperm are spherical and loosely and irregularly arranged, leading to more gaps between the starch granules. As a result, the maximum rupture force and elastic modulus of the farinaceous endosperm are relatively lower. The maximum rupture force of the farinaceous endosperm is 38 N, and the elastic modulus is 136 MPa. Compression tests were conducted on maize kernels, and scanning was performed using a Micro CT system. The results showed that the farinaceous endosperm deforms and breaks more easily, with most damage beginning in the farinaceous endosperm and then extending further. The micromechanics discrete element analysis of the loading process of the farinaceous endosperm was carried out further. It was found that the deformation of the farinaceous endosperm occurs in four stages: initial, crack initiation, crack propagation, and fracture. When the farinaceous endosperm is loaded to 132 N, internal cracks begin to initiate and gradually propagate. At 292 N, the internal particles of the farinaceous endosperm start to break, followed by a drop in load and eventual fracture. During the loading process, significant differences in the velocity field of the farinaceous endosperm were observed.